Recurrence of primary spontaneous pneumothorax. Issue 9 (September 1997) - Sadikot, R T; Greene, T; Meadows, K; Arnold, A G
Abstract : BACKGROUND: Primary spontaneous pneumothorax (PSP) is a common clinical problem and its incidence is thought to be increasing. The risk of recurrence is high and various studies quote rates of 20-60%. Factors which may or may not predispose to recurrence have not yet been established. METHODS: In a study period of four years 291 cases with a diagnosis of pneumothorax were reviewed; 153 patients with PSP were included in the study. Their risk of recurrence was analysed with particular reference to the following variables: age, sex, height and body mass index (BMI) of the patient, the initial size of pneumothorax, the smoking status of the patient, and the primary form of treatment employed. Univariate analysis was carried out by chi 2 testing and multivariate analysis was calculated by a logistic regression model. RESULTS: A retrospective study of 275 episodes of PSP in 153 patients over a four year period confirmed a high incidence of recurrence (54.2%). PSP was twice as common in men as in women, though women were significantly more likely to develop a recurrence (chi 2 = 7.58, df = 1, p < 0.01). Male height was the second most important factor, and smoking cessation the only other variable which significantly influenced the risk of recurrence. CONCLUSIONS: Analysis of several potential risk factors revealed that recurrence was not related to the BMI of the patient, the initial treatment of the pneumothorax, nor to its size. Recurrence was more common in taller men and in women. Smoking cessation appeared to reduce the risk of recurrence. These findings are discussed in the context of the possible aetiology of spontaneous pneumothorax, recurrences, and the management thereof.